The antibacterial activities of acetone and methanol extracts of hibiscus rosa sinensis leaves / Nur Fatin Nabila Anuar - Anuar, Nur Fatin Nabila (2013)
The aim of the study was to investigate the antibacterial activity of acetone and methanol extracts of Hibiscus rosa sinensis leaves. Crude extracts of the plant with acetone and methanol were screened for antibacterial activities against eight pathogenic bacteria which consisted of four Gram positive bacteria (Staphylococcus aureus, Methicillin-resistant Staphylococcus aureus, Streptococcus agalactiae, Streptococcus pyogenes) and four Gram negative bacteria (Pseudomonas aeruginosa, Escherichia coli, Klebsiella pneumonia, Shigella spp.). The in vitro antibacterial activity was performed by broth microdilution method. The result showed that acetone extract exhibited the highest antibacterial activity against Staphylococcus aureus with the lowest MIC value was found to be 6.25 mg/ml. However, methanol extract did not exhibit any antibacterial activity against all of the tested bacteria. The result obtained in the present study suggested that the acetone extract of H. rosa sinensis leaves exhibited better antibacterial activity as compared to the methanolic extract.